Pembuatan Perangkat Lunak Sistem Informasi Penjualan Tunai Berbasis WEB Di PT. Propan Raya Cirebon - Petrus sokibi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
he rapidly Technology Progress, especially in Computer, is very useful to the human in doing their job. Nowadays, the global era, every business needs a tool, Computer, to support their activities, especially to process data and information. In this research, the writer presents the topic titled: â€The Building of Software for Information System in Cash Selling by using WEB at PT. Propan Raya Cirebonâ€ as the development of the existing system from manual to the computerized system. This system is built by using PHP language program and MySql as the database storage. In this application, the user can process the selling transaction, input goods, and consumer data. When the transaction is being processed, the system will process the updating of stock in the database automatically, meanwhile, the user can determine the stocking in the store directly. Based on the research done on the trial, the Information system of cash selling has been successfully processed.